Transition in the critically ill patients: Malaysian nurses’ perspective - Mohamed Ludin, Salizar; Arbon, Paul; Parker, Steve (2010)
Background: The concept of transition is one of the concepts that are central to the nursing discipline. Hence, nurses understanding and experience in caring for critically ill patients undergoing transition are important to promote smooth transition and prevent negative long term outcomes to the patients. Knowledge on patients’ transition through the nurses’ could be useful and helpful in understanding and helping nurses to value and intervene nursing therapeutic for the patients experiencing transition. This paper represents part of a study on the nurses’ perception of the meaning of transition in the critically ill patients and the effects to the patients, families and nurses themselves.